Pengaruh Financial Literacy dan Overconfidence terhadap Pengambilan Keputusan Investasi Saham Generasi Milenial di Indonesia - Gabriela Sunjono; Nanik Linawati (Sanskara Manajemen Dan Bisnis, 2022)
In making investment decisions, it is necessary to have a thorough rationale based on the financial literacy of investors. However, the financial literacy possessed by Indonesian people is still relatively low. This means that there are other factors that influence stock investment decisions, one of which is overconfidence. Therefore, this study aims to see whether there is an influence of financial literacy and overconfidence on stock investment decisions made by millennials in Indonesia. The sample determination method uses a purposive sampling method with sample criteria namely millennial stock investors with an age range of 22-42 years. The analysis will be carried out using the Sem-PLS program. The novelty of this research lies in examining the tendency of overconfidence bias in stock investors who are millennials.